A Historical Study on the Properties of the Royal Family in Begémedir and Semén Teklay Gizat (Province): 1941-1974 - Eskezia, Geremew (Ethiopian Journal of Social Sciences, 2025)
The former Begémdir and Semén Teklay Gizat (province) was a key source of wealth for the royal family between 1941 and 1974. Despite its significance, studies on royal properties remain scarce. This research examines the conditions and significance of these properties during that period. Both primary and secondary sources were utilized, with archival materials from the former North Gondar Zone administration office proving particularly valuable. Data were carefully selected, cross-checked, described, and interpreted. The findings indicate that the royal family, and high-ranking government and military officials connected to them through marriage, leveraged their positions to amass wealth through land, housing, and the expanding commercial activities in Gondar. To manage the properties acquired from the Teklay Gizat, they relied on local agents, representatives, and overseers. The analysis highlights the strategies employed by the royal family and their agents in managing these assets and discusses the broader implications of such practices for understanding the interplay between property, power, and local development during the late imperial era of Ethiopia.Keywords: Royal properties, Overseers, Land, Housing, Property management